Andean medicinal plants for skin diseases: traditional uses, phytochemistry, and pharmacological profile - Ruiz Proaño, Erika Salomé (2023)
Skin conditions are considered a severe public health problem. However, conventional medicine based on a single compound fails to provide efficient clinical responses and low-cost drugs without side effects to various dermatological pathologies. The Andes possess one of the most pronounced flora biodiversity in the world, being a vast home of secondary metabolites active against different diseases. Thus, this literature review explores the ethnobotanical knowledge of Andean medicinal plants, both endemic and introduced species, and aims to summarize the findings of research activities for treating skin diseases. The methodology consists of identifying and selecting Andean medicinal plants that meet ethnobotanical studies and pharmacological information criteria. The literature review revealed the ethnobotanical use of 116 plant species belonging to 61 botanical families to treat skin conditions. The most traditionally used families are the Asteraceae (13%), Lamiaceae (7%), Fabaceae (5%), Anacardiaceae (4%) and Poaceae (3%), widely distributed in the Andes. The medicinal plants were primarily prepared through infusions of leaves and were administered topically by the Andean people. The phytochemical studies revealed that the main classes of active secondary metabolites were phenolic compounds and terpenes. Besides the pharmacological studies of Andean medicinal plants and their herbal formulations showed enhanced biological properties, which are relevant for treating and preventing skin conditions but also for skin care.